The Role of Local Government Organizations in Addressing the Problems of Out-of-School Youth in Khuean Bang Lang Subdistrict Municipality, Bannang Sata District, Yala Province - หะยีแวนิ, ฟาดีละห์; จิ, ฮัสเซียณีย์; ดาราหิง, อิฟฟาน; มินทราศักดิ์, นินุสรา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to: 1. examine the factors contributing to children and youth dropping out of the education system; 2. investigate the roles of local administrative organizations in addressing the issue of out-of-school youth; and 3. propose appropriate models and approaches for driving mechanisms to support, assist, and develop out-of-school youth in accordance with the context of Khuean Bang Lang Subdistrict Municipality, Bannang Sata District, Yala Province. This study employed a qualitative research methodology. Data were collected through in-depth interviews and focus group discussions with 22 participants, including community leaders, parents, and local residents. The data were analyzed using content analysis.            The findings revealed that: 1. Factors contributing to youth dropping out of the education system include family-related factors such as unstable family structures and lack of support; economic factors such as poverty and unstable income; and individual factors such as lack of motivation, negative attitudes toward education, and social environmental influences. 2. Regarding the roles of local administrative organizations, they were found to play important roles in coordination, resource support, and organizing educational and vocational training activities for youth. However, there is still a lack of systematic and clearly defined operational mechanisms. 3. In terms of development approaches, it was found that there should be proactive systems for identifying and monitoring out-of-school youth, integrated collaboration among all sectors, and flexible learning models that align with the local context in order to promote sustainable youth development.